Pengaruh pengetahuan perempuan pasangan usia subur terhadap upaya melakukan deteksi dini kanker serviks - Nurul Soimah (Jurnal Kebidanan, 2020)
Cervical cancer is a malignant disease that attacks the female uterine organ. Data of Health Office D.I. Yogyakarta 2014 show that most cancer sufferers come from age 25 -64 years, adolescents 15-24 years, The study was conducted in order to know the effect of knowledge on women of childbearing age efforts to conduct early detection of cervical cancer, the explanatory research design of The One Group Pretest-posttest Design experimental study without a control group. The study population in the Aisyiyah recitation group 'Aisyiyah Hamlet Ganggom, Bangunkerto, Turi, Sleman, the total population of 31 people, sampling techniques in total sampling, obtained a sample of 26 respondents who have met the inclusion criteria of women of reproductive age 20-35, educated at least graduated from junior high school, data collection using the adoption questionnaire from Setianingsih and Soimah, (2017), univariate analysis calculated percentage, bivariate using Wilcoxon test. The highest age characteristics of 20-30 years old amounted to 14 (53.8%) respondents, Educational factors most of the last high school education totaled 19 people (73%), the highest level of knowledge before counseling was 14 people (53.8%). after counseling, knowledgeable EFAs were increasing to 21 people (80.8%). Wilcoxon test knowledge of pre and post counseling with prevention efforts obtained with a value of p = 1.34> α (0.05) can be concluded that there is no effect of counseling on knowledge of EFA to changes in the behavior of prevention of early cervical cancer.